Development of a robust and semi-automated two-step antibody purification process. Issue 1 (1st January 2021) - Yang, Xiaomin; Yuan, Richard; Garcia, Christopher; Berry, Jessica; Foster, Denisa; He, Dongmei; Zhang, Gui-Feng; Jones, Bryan E.
ABSTRACT: Advances in antibody discovery technologies, especially with the availability of humanized mice and phage/yeast library approaches, enable the generation of a large diversity of antibodies against nearly any target of interest. As a result, there is an increasing demand for the production of larger numbers of purified antibodies at quantities (10s-100s of milligrams) sufficient for functional screening assays, drug-ability/develop-ability studies and immunogenicity assessments. To accommodate this need, new methods are required that bridge miniature high throughput/plate-based purification and conventional, one at a time, two-step purification at much larger scales. Thus, we developed a semi-automated, mid-scale (i.e., 1–75 mg) purification process that uses a combination of parallel affinity capture and automated sequential polishing to provide substantially improved throughput while delivering high purity. We optimized the affinity capture step to perform 24 monoclonal antibody purifications in parallel using a Protein Maker for 20–200 mL culture media. The eluant is transferred directly to an AKTA pure system equipped with an autosampler for sequential preparative size exclusion chromatography to remove aggregates and undesirable impurities, as well as exchange the antibody into a buffer suitable for most uses, including cell-based assays. This two-step purification procedure, together with plate-based protein analytical methods, can purify 24–48 monoclonal antibodies in <20 hours and generate up to 80 mg per sample. A stringent clean-in-place protocol for both systems and column maintenance was designed and established to minimize endotoxin contamination. This process has proven to be very reliable and robust, enabling the production of thousands of antibodies of sufficient quality and quantity that are suitable for cell-based assays, biochemical/biophysical characterization, and in vivo animal models.